Trace and rare earth element distribution in hyperalkaline serpentinite-hosted spring waters and associated authigenic carbonates from the Ronda peridotite - Zwicker, Jennifer; Smrzka, Daniel; Vadillo, Iñaki; Jiménez-Gavilán, Pablo; Giampouras, Manolis; Peckmann, Jörn; Bach, Wolfgang (Applied geochemistry, 2022)
The Ronda peridotite in southern Spain is subject to low-temperature serpentinization by circulating groundwaters that produces hyperalkaline fluids of high pH and low dissolved inorganic carbon content (DIC). When these waters resurface as hyperalkaline springs they take up atmospheric carbon dioxide (CO2), which triggers the precipitation of travertine carbonates. Spring waters at Baños del Duque, Fuente Romana, and Fuente Amargosa show typical chemical features of hyperalkaline springs such as high pH and low DIC, yet exhibit an unusual distribution of rare earth elements (REEs) enriched in lanthanum (La) and cerium (Ce). In order to constrain changes in spring water chemistry and carbonate precipitation during atmospheric CO2 uptake, a reaction path model was set up to illustrate that the distribution of REE species in the high pH and low DIC water is strongly dependent on REE complexation by hydroxide and carbonate species. Reaction path modeling results show that during spring fluid emission and CO2 uptake, REE speciation in the fluids shifts from a dominance of hydroxide to carbonate complexes. The complexation of rare earth elements in the high pH, low DIC fluids strongly depends on the DIC content of the respective fluid. The REE distribution of travertine deposits associated with the hyperalkaline springs deviates from that in the fluids, suggesting that travertines precipitated from fluids different to those currently emitted from the springs. First detailed investigation of rare earth elements in hyperalkaline spring fluids. Hyperalkaline spring fluids associated with onshore low-temperature serpentinization. Geochemical modeling shows an unusual rare earth element speciation distribution. Preferential incorporation of MREEs and HREEs into travertine carbonates.